THE STYLISTIC ANALYSIS OF ALICE MUNRO’S "CARRIED AWAY" - Dhuha A. Hammadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to identify and analyze Alice Munro’s short story collection ’Open Secrets’, specifically the first tale of ’Carried Away’ which is called ’Letters", from a syntactic stylistic perspective. The model adopted in the study is G. Leech and M. Short (2007). The syntactic devices that are specialized for the study are the sentence type, its complexity, the clause types, and the verb phrases. The sentence complexity only includes two devices in the study: the sentence length and the independent and dependent clauses. The study plans to evaluate the frequent use of some syntactic stylistic features in Munro’s short story and to identify the most common syntactic stylistic devices utilized in it. The result of the study reveals that the most dominant sentence type is the statement sentence among the others to make the readers interpret and understand it easily and clearly. Secondly, analyzing the sentence complexity for each paragraph of the story, the paragraph (20) is the most length sentence out of the first part of the story. The highest ratio of the dependent clauses to independent ones is existed in paragraph (4). Thirdly, although a variety of clause types are utilized in the data, the adverbial clauses occupy the first place among the others to give additional descriptive details and information to the readers. Finally, the verb clauses with different tenses are widely used and the past tense is the dominant one in the story to tell the story events that happened in the past.